The demand-pull efect of public procurement on innovation and industrial renewal - Francesco Crespi; Dario Guarascio (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2017)
This article analyzes, empirically, the link between public procurement and innovation activities by taking into account the moderating effect played by import penetration on public procurement. Using industry-level information on patent applications for 24 countries over the period 1995-2012, we test the impact of public procurement on innovation activities and whether and in which direction import penetration on public procurement impacts on patenting. The econometric analysis relies on Poisson regression techniques aiming to investigate the correlation between patent counts, supply as well as demand-side determinants, controlling for country and sector heterogeneity. The obtained results confirm our main hypotheses. The dynamics of patenting is positively affected by the public procurement while a high degree of import penetration reduces the innovation enhancing effect exerted by public demand. Our results suggest that public demand may represent an effective tool for industrial policy to stimulate innovative activities, to shape the transformation of production systems and to foster industrial renewal. Moreover, the empirical evidence shows that the strategy regarding the degree of openness in public procurement towards non-domestic firms is a crucial policy choice capable of affecting the innovative potential of public demand.
Keywords: O25; O30; O31; O49; 330; Public procurement; innovation policy; demand-side innovation policy